2021
DOI: 10.47836/pjst.29.3.30
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Compounds, Proximate Compositions and Assessment of Free Radical Scavenging Activities of Nypa Fruticans Wurmb. Sap

Abstract: Nipa palm sap (NPS) as source of medicine traditionally used to treat various diseases. This study identified good radical scavenging activity in NPS with the IC50 value of 33.36 μg/mL using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. NPS comprises of moisture (72.44%), ash (1.04%), protein (7.04%), carbohydrate (19.48%), fat (0%), and energy level (106 kcal). Glucose (0.3%) and fructose (1.8%) were detected using high-performance liquid chromatography. Maleic acid, cinnamic acid, chlorogenic acid, and kaempf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
1
0
1
Order By: Relevance
“…Dalam sistem biologis, senyawa fenolik dan flavonoid berperan sebagai agen penangkap radikal bebas (Lourenço et al, 2019). Menurut Yahaya et al (2021) asam askorbat di nipah menunjukkan aktivitas antioksidan tertinggi dengan nilai IC 50 21,29±0,74 g/mL. Menurut Sowndhararajan dan Kang (2013) semakin rendah IC 50 semakin tinggi aktivitas antioksidannya.…”
Section: Penggunaan Sebagai Obatunclassified
“…Dalam sistem biologis, senyawa fenolik dan flavonoid berperan sebagai agen penangkap radikal bebas (Lourenço et al, 2019). Menurut Yahaya et al (2021) asam askorbat di nipah menunjukkan aktivitas antioksidan tertinggi dengan nilai IC 50 21,29±0,74 g/mL. Menurut Sowndhararajan dan Kang (2013) semakin rendah IC 50 semakin tinggi aktivitas antioksidannya.…”
Section: Penggunaan Sebagai Obatunclassified
“…Several studies related to the nipa palm plant, namely nipa flower stalk extract, have demonstrated its anti-pain and anti-inflammatory activity by suppressing TRPV1 in sciatic nerve injury [ 82 ]. The phytochemical content of the nipa palm plant includes phenolics, alkaloids, tannins, flavonoids, terpenoids, steroids, and saponins [ 83 ]. Nipa palm sap contains phenolics and flavonoids; the fruit skin contains polyphenols and tannins, and the seeds contain alkaloids [ 84 ].…”
Section: Arecaceae and Its Potential As A Source Of Natural Anti-oa C...mentioning
confidence: 99%